Climate change adaptation in developed nations from theory to practice - Ford, James D. (Advances in global change research, 2011)
Section I: Introduction and overview -- Section II: Adaptation in the public health sector -- Section III: Adaptation in the industrial sector -- Section IV: Adaptation in the urban environment -- Section V: Adaptation in the agricultural sector -- Section VI: Adaptation in rural and resource-dependent communities.-  Section VII: Future directions -- Index.